Who prefers what? Correlates of preferences for next‐generation HIV prevention products among a national U.S. sample of young men who have sex with men - Katie B. Biello; Pablo K. Valente; Daniel Teixeira da Silva; Willey Lin; Ryan Drab; Lisa Hightow‐Weidman; Kenneth H. Mayer; José A. Bauermeister; the iTech Team (Journal of the International AIDS Society, 2023)
Abstract Introduction Pre‐exposure prophylaxis (PrEP) has been available for young people for over a decade, yet only ∼15% of young people in the United States with indications for PrEP have a prescription for it. Next‐generation PrEP modalities may address some of the challenges of daily oral PrEP. However, preferences for these products are unknown. Methods From October 2020 to June 2021, we conducted an online survey of 737 cisgender, young men who have sex with men (age 15–24 years) without HIV across the United States who reported same‐sex attraction or consensual sex with another man in the past 6 months. Participants completed a conjoint experiment comparing daily oral pills, event‐driven oral pills, event‐driven rectal douches, intramuscular injections, intravenous broadly neutralizing antibody (bnAb) infusions and subcutaneous implants. Participants ranked the products from most to least preferred. Exploded logit models examined the association between ranked preferences of PrEP modalities and socio‐demographic and behavioural characteristics. Results Participants’ mean age was 21 years (SD = 2.3), and 56% identified as White. Nineteen percent were currently taking daily oral PrEP, and another 9% had previously taken it. Participants prioritized efficacy, absence of side effects and costs in the conjoint analyses. Daily oral PrEP had the highest preference ranking, followed by event‐driven oral (OR = 0.89, p = 0.058), injectable (OR = 0.83, p = 0.005), implant (OR = 0.48, p < 0.0001), bnAb infusions (OR = 0.38, p < 0.0001) and rectal douches (OR = 0.24, p < 0.0001). There were differences in PrEP preferences across age, insurance status, sexual behaviour, PrEP use history, HIV and sexually transmitted infection (STI) testing history, and STI diagnoses (omnibus tests: p < 0.05). Participants also provided reasons for selecting their top product choice: ease of use for those who chose daily oral (99%) and daily event‐driven (98.5%); feel more protected against HIV for those who chose injectable (95.4%) and implants (100%); not worrying about forgetting to take it for those who chose bnAbs (93.8%); and being able to stop taking it when they want for those who chose rectal douche (90.9%). Conclusions Next‐generation modalities were less likely to be preferred over daily oral PrEP, with differences in the magnitude by socio‐demographic and behavioural characteristics. Given the low uptake of daily oral PrEP, end‐users’ preferences for and concerns about PrEP products must be understood to ensure high acceptability and penetration.